Effect of watching professional baseball at a stadium on health‐related outcomes among Japanese older adults: A randomized controlled trial. Issue 8 (16th May 2019) - Kawakami, Ryoko; Sawada, Susumu S; Ito, Tomoko; Gando, Yuko; Fukushi, Tomohiro; Yoshino, Atsushi; Kurita, Satoshi; Oka, Koichiro; Sakamoto, Shizuo; Higuchi, Mitsuru
Abstract : Aim: Watching sports at stadiums can have a favorable impact on health‐related outcomes in older adults. We examined the effect of watching professional baseball at a ballpark on older adults' health‐related outcomes. Methods: A total fo 58 participants aged 65–85 years were randomized into a spectator group ( n = 29) and waiting‐list group ( n = 29). During the 2‐month intervention, there were 21 games. The spectator group watched games at the ballpark, and the waiting‐list group maintained their daily routines. The health‐related outcomes were executive and cognitive functions, health‐related quality of life, depression symptoms, subjective happiness and physical activity. Results: The median days watching baseball games in the spectator group was 6 days (interquartile range 4–10 days). Executive function using the reverse Stroop interference rate showed a non‐significant trend of improvement in the spectator group compared with the waiting‐list group ( P = 0.063). The spectator group showed a significant reduction in depressive symptoms compared with the waiting‐list group ( P = 0.016). Conclusions: Regularly watching professional baseball at a ballpark reduced older adults' depression symptoms.Geriatr Gerontol Int 2019; 19: 717–722 .